Investigation of the kinetic characteristics of red blood cell acetylcholinesterase in ABO, Rh hemolytic disease of the newborn and thalassemia major cases - Özand, Pınar; Artvinli, Suat; Yarımağan, Sezer (The Turkish Journal of Pediatrics, 1970)
Various kinetic parameters of erythrocyte acetylcholinesterase in normal cases and patients afflicted with ABO or Rh hemolytic disease or thalassemia major have been investigated. No evidence for the presence of a variant enzyme was found. However, the maximal velocity was lower in normal newborns and was more pronounced in ABO hemolytic disease. A delayed appearance of enzyme protein is speculated to be the explanation for this.